1992
DOI: 10.1677/joe.0.1350597
|View full text |Cite
|
Sign up to set email alerts
|

Retention of normal ovarian function after hysterectomy

Abstract: What are the long-term effects of hysterectomy on the ovaries of normal women? Ninety-three women aged 29-44 years (median, 38 years) who had undergone hysterectomy for benign reasons 0.3-9.1 years prior to investigation, contributed urine samples twice weekly for a period of 53-149 days (median 102 days) for pregnanediol analysis. The interval between successive pregnanediol peaks and their increment over baseline were measured. The median peak interval was 27.3 days, and 93.3% of all intervals were of 21- to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In nonprimate species of mammals, luteal regression is initiated by a luteolytic factor, believed to be prostaglandin F 2a , secreted by the uterus if timely pregnancy does not ensue [Stouffer, 2006]. However, this is not the scenario in macaques or women because hysterectomy does not result in cessation of normal menstrual cyclicity or abnormally long luteal phases [Castracane et al, 1979;Metcalf et al, 1992]. Likewise, removal of the uterus in vervet monkeys did not alter the patterns of ovarian steroid secretion or ovarian cyclicity.…”
Section: Discussionmentioning
confidence: 99%
“…In nonprimate species of mammals, luteal regression is initiated by a luteolytic factor, believed to be prostaglandin F 2a , secreted by the uterus if timely pregnancy does not ensue [Stouffer, 2006]. However, this is not the scenario in macaques or women because hysterectomy does not result in cessation of normal menstrual cyclicity or abnormally long luteal phases [Castracane et al, 1979;Metcalf et al, 1992]. Likewise, removal of the uterus in vervet monkeys did not alter the patterns of ovarian steroid secretion or ovarian cyclicity.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that only 18-9 % of a representative sample of a population of hysterectomized women complained of PMS and that only 2-6% had confirmed PMS (Braiden & Metcalf, 1994). We have shown that the removal of the uterus makes little difference to the ovarian hormone cycle (Metcalf et al 1992a). We have also shown that six of a group of seven women who had regular premenstrual symptoms before hysterectomy, lost their cyclical symptoms following surgery but preserved their ovarian hormone cycle (Metcalf et al 1992ft).…”
mentioning
confidence: 77%
“…In this report, four of the seven post-hysterectomy women, whose MR images suggested active ovarian function, actually showed physiological FDG uptake in the ovaries. The phenomenon was expected because many investigators have reported that women of the reproductive age and whose ovaries are preserved showed normal ovarian function with a cyclic change of pituitary gonadotropins and ovarian hormones or ovulatory cycles after hysterectomy [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%